Is helicopter transferal in the “drip-and-ship” approach for endovascular treatment the better choice? A retrospective analysis of transfer times - Lagno, Evgeniia; Ernst, Johanna; Flemming, Andreas; Raab, Frauke; Götz, Friedrich; Brauckmann, Vesta; Macke, Christian; Worthmann, Hans (Frontiers in Neurology, 2025)
BackgroundFor patients with large vessel occlusion (LVO) admitted to primary stroke centers (PSC) without neuro-interventional capabilities, timely transfer to comprehensive stroke centers (CSC) is crucial. In this study, we compared the transport time of ground- and air-based transfer for patients receiving endovascular treatment at our CSC.MethodsIn a retrospective cohort study, consecutive ischemic stroke patients with LVO who were transferred ground- or air-based to our CSC between October 2018 and December 2022 were examined. 170 patients with LVO from five PSCs within a radius of 55 to 85 km to the CSC were included. Patients were transported either with an emergency rescue helicopter (ERH), a ground ambulance (GA), GA accompanied by an emergency physician vehicle (EPV), or in a mobile intensive care unit (MICU) and were accordingly divided into air-based (61 patients) and ground-based (109 patients) main transport groups.ResultsThe analysis revealed a significant difference between air- and ground-based transport groups (75 vs. 82 min, p = 0.01). After calculating the transport time in relation to the covered ground distance, air-based transport was shorter by a median of 0.15 min per kilometer. In a comparison of the individual means, ERH was faster than GA and EPV (both p < 0.001). Only few transports were done by MICU and they mainly showed very long transfer times. The complication rates were generally low with only minor complications and no deaths reported in both groups. However, they were more frequently observed in the land-based transport group (20.2% vs. 8.2%, p = 0.04).ConclusionIn the present analysis, air-based transport was faster than ground-based transport for the secondary transfer of patients with stroke due to LVO in the observed regional conditions. Both air- and land-based transport appear to be safe. No serious complications occurred during transport, while complications were more frequent in the ground-based transport group.